Surgical Treatment of a Catheter-Induced Iatrogenic Dissection of the Right Coronary Artery following Cardiac Catheterization - Panagiotis Artemiou; Stefan Lukacin; Peter Kirsch; Jan Ignac; Boris Bily; Alzbeta Tohatyova; Miroslava Bilecova-Rabajdova; Frantisek Sabol (Journal of Tehran University Heart Center, 2016)
Iatrogenic dissections of the ascending aorta are an uncommon and severe complication during cardiac catheterization. A 68-year-old female patient underwent diagnostic cardiac catheterization due to non-ST-elevation myocardial infarction. During the procedure, a catheter-induced 360• Class I dissection of the right coronary artery occurred. The patient developed severe bradycardia, which was treated with a temporary pacemaker. She underwent an emergency operation with ligation and a saphenous vein graft in the right coronary artery. The postoperative course was uneventful; and on postoperative day 6, she was discharged home.